La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Blue Oil, premier groupe punk féminin au Québec - Desfossés, Félix B. (Ici Radio-Canada, 2019)

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)
Publisher: University of Nebraska Press

Radical Queers: A Pop Culture Assessment of Montréal's Anti-Capitalist Ass Pirates, the Panthères roses, and Lesbians on Ecstasy - Hogan, Mélanie (Canadian Woman Studies, 2005)
Cet article nous explique comment des artistes montréalaises queer radicales, Anti-Capitalists Ass Pirates, les Panthères roses et Lesbians on Ecstasy, ont transformé la sphère publique en intégrant politique et célébrations dans leurs importants messages à la population.

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)